Analysis Of Management Accounting Implementation In Cost Planning And Control In The Retail Industry (Case Study At CV. Arafa Berkah Indonesia) - Tiara Endriani; Andri Indrawan; Evi Martaseli (LPPM Universitas Buddhi Dharma, 2026)
The Indonesian retail industry is experiencing dynamic transformation driven by advanced technology adoption, digitalization, and changing consumer behavior, with Technavio (2024) projecting industry revenue to surge to approximately USD 49.56 billion with a compound annual growth rate (CAGR) of 4.73% from 2024 to 2028. Despite significant growth opportunities, the retail sector faces complex challenges including intense competition, inventory and supply chain management issues, high operational costs, economic volatility, and regulatory compliance, making retail businesses vulnerable to cost pressures that encompass rental expenses, labor costs, logistics, and digital marketing expenses. This research aims to analyze the application of management accounting in cost planning and control at CV. Arafa Berkah Indonesia, a retail company operating in the fashion industry, evaluating the extent to which management accounting methods have been implemented and identifying constraints faced in their implementation through in-depth data analysis and examination of relevant theoretical concepts. The study reveals that CV. Arafa Berkah Indonesia has successfully implemented management accounting in cost planning and control, with the company's information system generating relevant data that significantly influences managerial decision-making. The implementation of Activity-Based Budgeting (ABB) method in cost planning assists the company in designing budgets according to activities in each division, while the use of Activity Variable Cost method in cost control supports the company in adjusting expenditures to dynamic activity volumes and market demands, with effectiveness reflected through the application of management accounting indicators across various cost types, serving as a foundation for sustainable strategy formulation. Although management accounting implementation operates optimally, the company still encounters several constraints including adjustment challenges with budget control applications and fluctuations in variable costs, particularly digital advertising costs caused by dynamic advertising competition levels and social media platform algorithms, which can affect pre-designed cost planning when actual costs exceed established budgets, requiring companies to rapidly readjust their strategies.